Effect of thermal history on the phase behavior of N-methyl morpholine N-oxide hydrates and their solutions of cellulose - Kim, DB; Lee, WS; Jo, SM; Lee, YM; Kim, BC (SOC POLYMER SCIENCE JAPAN, 2001)
N-Methyl morpholine N-oxide (NMMO) hydrates, used in the preparation of cellulose spinning dope for lyocell manufacturing, have Various crystal structures according to the hydration number (n). A single melting peak for solid-solid transition from NMMO monohydrate to anhydrous NMMO at 94 degreesC was previously reported. However, we observed the melting peak at 90 degreesC ascribed to the solid-solid transition from NMMO monohydrate to anhydrous NMMO and another melting peak observed in the range from 98 to 105 degreesC when n < 1. This discrepancy resulted from the experimental errors in differential scanning calorimetry (DSC) measurement. The pressure capsule enabled us to obtain precise and reproducible DSC data of NMMO hydrates. The three different crystal structures of NMMO hydrates with n < 1 were identified by crystallization experiments. The crystal, which had melted in the range from 90 to 105 degreesC during heating (shown by double peaks), was recrystallized at 80 degreesC during cooling, which has never been reported. The NMMO hydrates with n < 1 required heating above 130<degrees>C to produce a homogeneous melt, and the required temperature was increased up to 180 degreesC for anhydrous NMMO. if the heating temperature was not high enough to fully melt the NMMO hydrate crystal, the unmelted NMMO hydrate crystals affected the thermal responses of the hydrate and its phase behavior of cellulose solutions in the NMMO hydrate.
Keywords: PHYSICAL-PROPERTIES; FIBERS; SOLVENT; SYSTEM; WATER